Analisa Pengendalian Sedimen Pada Daerah Irigasi (Studi Kasus Medan Amplas) - Hariyati Lubis (Penerbit Yayasan Daarul Huda Kruengmane, 2021)
One potential control strategy that supports the provision of agricultural facilities and infrastructure is water resource management. A weir is a type of building that is much smaller than other buildings, which causes water to pool to form a pool but is able to pass through the top of the weir, or mercu. Operation and Maintenance (O&M) activities of weir buildings are a weir construction problem that often occurs in Indonesia. The problem with the weir in Medan Amplas is that the weir pond cannot accommodate the volume of water because there is too much sedimentation. Irrigation systems are usually used to supply water from rivers to rice fields, so that plants do not lack water in the dry season and not too much water in the rainy season. Rivers in Indonesia usually carry sediment, both bottom sediment and floating sediment. Since the elevation at the river bed is +23.8, topographic measurements indicate that hydraulic flushing is not feasible. Meanwhile, the elevation at the end of the sand trap plan which allows flushing is + 22.6. Therefore, hydraulic flushing is not possible. Therefore, flushing will be done mechanically or manually. Due to the dominant type of sand sediment at the location, it is planned that sediment with a diameter of 0.140 mm will be deposited. By building mud bags, sediment will be collected first in the mud bags and will not enter the prime channel, so that the tamping capacity of the channel is not disturbed by sediment. As a result, urban irrigation areas can be irrigated.